Clinical Outcomes of Intrauterine Insemination for Male Infertility in Brunei Darussalam - Aeryza Sufiri; Rehana Rehman; Faiza Alam (Aziz Fatimah Medical and Dental College, 2024)
Objectives: This study aims to evaluate the factors influencing the success of Intrauterine insemination (IUI) in infertile patients due to male causes in Brunei Darussalam. Methodology: Pre-diagnosed male infertility patients of all ages were included in this retrospective cohort analysis from the "Raja Isteri Pengiran Anak Saleha (RIPAS) Hospital's" Brunei Darussalam between January 2015 and December 2020. South Asian criteria were used for BMI categorization. Statistical evaluation of the data was conducted utilizing R-studio. Results: Out of 240 research participants, 92.1% were Malay. IUI resulted as a successful pregnancy for 18 males (7.5%), while 222 subjects (92.5%) had unsuccessful conception. The semen parameters were correlated with age and BMI. Although the difference was statistically insignificant, the male subjects with successful outcomes after IUI were young, BMI was less, and the semen quality variables were better than the male subjects who had unsuccessful outcomes. Conclusion: The male study subjects with the outcome of successful IUI resulting in pregnancy were younger, and had lower BMI and better semen parameters than the group in which IUI failed to result in pregnancy.